ASSOCIATION BETWEEN ARITHMETIC MEAN AND GEOMETRIC MEAN - Abdullayeva Gulasal Abdumo‘Minovna (Bright Mind Publishing, 2025)
This article explores the association between the arithmetic mean and the geometric mean. It examines their mathematical properties, comparative values, and applications in problem-solving. The study highlights the conditions under which the arithmetic mean is greater than or equal to the geometric mean, illustrating the significance of this association in various mathematical and real-life contexts.
Keywords: Arithmetic mean, geometric mean, inequality, mathematical analysis, applications.